INSTRUCTIONAL MEDIA IN TEACHING ENGLISH TO YOUNG LEARNERS: A case study in elementary schools in kuningan - Aini, Wildan Nurul (2013)
This research entitled "Instructional Media in Teaching English to Young Learners" was aimed to investigate (1) the use of instructional media by the teachers in teaching English to young learners; (2) the problems that they encounter in using instructional media; also (3) problem solving of the media utilization problems. This study was conducted in elementary schools in Kuningan. To collect the data, the researcher employed observation and interview techniques. The result of the study indicates that there are four types of instructional media which are generally used by the teachers, comprising: (1) boards; (2) realia; (3) pictures; and (4) books. Each of them is used in various ways. Meanwhile, the teachers faced problems in both process of selecting and using instructional media. The strategy used to solve the problems during selection process was utilizing available media. Meanwhile, to overcome the problem during the use of instructional media were by requesting technician help, borrowing instructional media supply from other class and preparing back-up instructional media. Key terms: Instructional media, media utilization, media selection, problem solving of media utilization problems, young learners. Penelitian ini yang berjudul "Instructional Media in Teaching English to Young Learners" bertujuan untuk mengetahui (1) penggunaan media pembelajaran oleh guru dalam mengajar bahasa Inggris untuk anak-anak; (2) masalah-masalah yang para guru hadapi dalam menggunakan media pembelajaran; juga (3) pemecahan masalah terhadap masalah-masalah yang dihadapi dalam penggunaan media pembelajaran. Penelitian ini dilaksanakan di beberapa sekolah dasar di daeran Kuningan. Untuk mengumpulkan data, peneliti menggunakan observasi dan wawancara. Hasil penelitian menunjukkan bahwa ada empat jenis media pembelajaran yang pada umumnya digunakan oleh para guru, yaitu: (1) papan tulis; (2) realia; (3) gambar; dan (4) buku. Masing-masing media pembelajaran tersebut digunakan oleh para guru dengan cara yang berbeda. Sementara itu, para guru menghadapi berbagai masalah baik dalam pemilihan maupun penggunaan media pembelajaran. Strategi yang digunakan untuk mengatasi berbagai masalah dalam proses pemilihan media adalah dengan menggunakan media pembelajaran yang sudah tersedia di sekolah. Sedangkan, untuk mengatasi masalah dalam penggunaan media pembelajaran adalah dengan meminta bantuan dari teknisi, meminjam perediaan media pembelajaran dari kelas yang lain dan mempersiapkan cadangan media pembelajaran. Kata kunci: media pembelajaran, penggunaan media, pemilihan media, pemecahan masalah atas masalah penggunaan media, anak-anak.